Development and Evaluation of a Crop Residue Shredder - Osei, Seth (University of Cape Coast, 2024)
The study aimed at developing and evaluating a crop residue shredder. The components of the machine include a frame, hopper, shafts, electric motor, blades, sieve, spur gear, and outlet, to convert crop residues into a smaller form. The performance of the developed machine was evaluated using maize, millet and sorghum stalk, as feeding materials, with varying speeds of 55 rpm, 110 rpm and 220 rpm. The machine achieved a maximum shredding efficiency of 82% for maize stalk residues passing through a 20 mm diameter sieve, and the shredding speed was 220 rpm. The maximum throughput capacity attained was 14.6 kg/h of maize stalk at 220 rpm speed, while the minimum throughput was 5.14 kg/h of sorghum stalk at a speed of 55 rpm. The optimization of shredding speeds shows significant energy savings, as demonstrated by reduced power consumption at higher speeds from 0.20 kWh to 0.10 kWh for maize and 0.25 kWh to 0.10 kWh for millet when speeds increase from lower to higher rpm. The particle size distribution of crop residues depends on shredding speed, with lower speeds (55 rpm) producing larger particles, medium speeds (110 rpm) creating balanced distributions ideal for composting, and higher speeds (220 rpm) generating finer particles for rapid decomposition. The machine is user-friendly to small scale farmers and could be useful for carrying around relevant residue size reduction operations in agriculture in Ghana and other Sub-Saharan Africa countries.
xx,134p:, ill.
Keywords: Crop residues; shredder; shredding efficiency; Agricultural machinery.